A time‐dependent density function theory study on the substituent effect on excited‐state intramolecular proton transfer of 4′‐methoxy‐3‐hydroxyl flavone. (16th April 2021) - Ni, Mei; Liang, Xiuning; Fang, Hua
Abstract: Theoretical investigations on the excited‐state intramolecular proton transfer (ESIPT) in the 4′‐methoxy‐3‐hydroxyl flavone (MHF) derivatives 4R‐MHF (R: COOH, CF3, and CN) are performed based on time‐dependent density function theory (TD‐DFT). According to our calculations, the intramolecular H bondings in 4R‐MHF (R: COOH, CF3, and CN) are weakened by the substituents, which would be unfavorable to ESIPT reaction. ESIPT processes in the 4R‐MHF (R: COOH, CF3, and CN) are slightly harder than that in MHF because the ESIPT barriers of 4R‐MHF (R: COOH, CF3, and CN) are on average 0.38 kcal/mol larger than that of MHF. The stronger the electron‐withdrawing ability, the larger is the ESIPT potential barrier. Abstract : The intramolecular H bond of 4R‐MHF (R: COOH, CF3, and CN) is obviously enhanced in the S1 state, which is favorable to take place ESIPT process. The electron‐withdrawing substituents weaken the intramolecular H bond and increase the ESIPT barrier in the 4R‐MHF. The stronger the electron‐withdrawing ability, the larger is the ESIPT potential barrier.